ІНТЕНСИФІКАЦІЯ НАВЧАЛЬНОЇ ДІЯЛЬНОСТІ СТУДЕНТІВ-АГРАРІЇВ (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2011)
The article presents the scientific research of the intensification of educational process of agrarian students.Motivation, activization of training, computer maintenance are the ways for improvement of training. The authorconsiders the necessity to introduce into practice innovative technologies, which are directed at the improvement ofeducational system and intensification of educational process.